2015
DOI: 10.1021/jp511157n
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization via the Covalent Bonding of Ta@Si16 Nanoclusters and C60 Molecules

Abstract: Initial products prepared via the surface immobilization of Ta-atom-encapsulated Si 16 cage (Ta@Si 16 ) nanoclusters on solid surfaces terminated with monolayer films of C 60 molecules were investigated using scanning tunneling microscopy (STM). The STM results indicated that marked aggregation and desorption of surface-immobilized Ta@Si 16 nanoclusters were not induced, even after thermal annealing at ∼500 K, whereas the local vertical and lateral positions of the Ta@Si 16 nanoclusters with respect to neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
(67 reference statements)
1
39
0
Order By: Relevance
“…Based on the principle of 68 electron shell closure, 12−14 the Ta@Si 16 nanocluster exhibits an alkali-like superatomic behavior, which promotes the release of one electron to produce the electronically stabilized monocation (Ta@Si 16 ) + . From the stoichiometric viewpoint, indeed, previous STM results have shown that the uppermost C 60 molecules provided a favorable adsorption site at deposition densities approximating 1 ML, 20 suggesting that Ta@Si 16 interacted with C 60 in a one-to-one manner. Since C 60 displays high electron acceptability, 34 the deposited Ta@Si 16 may be stabilized by formation of a superatomic CT complex of (Ta@Si 16 ) + C 60 − .…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on the principle of 68 electron shell closure, 12−14 the Ta@Si 16 nanocluster exhibits an alkali-like superatomic behavior, which promotes the release of one electron to produce the electronically stabilized monocation (Ta@Si 16 ) + . From the stoichiometric viewpoint, indeed, previous STM results have shown that the uppermost C 60 molecules provided a favorable adsorption site at deposition densities approximating 1 ML, 20 suggesting that Ta@Si 16 interacted with C 60 in a one-to-one manner. Since C 60 displays high electron acceptability, 34 the deposited Ta@Si 16 may be stabilized by formation of a superatomic CT complex of (Ta@Si 16 ) + C 60 − .…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 83%
“…Nakaya et al have recently observed an individual alkali-like Ta@Si 16 nanocluster on ordered electron-acceptable C 60 molecular film by scanning tunneling microscopy (STM), consistent with nanocluster immobilization. Furthermore, Ta@Si 16 readily forms the stoichiometric one-to-one Ta@Si 16 C 60 complex on C 60 films. , However, its exact chemical state, which is crucial for the treatment of M@Si 16 nanocluster-based CT complexes stabilized by counter molecules, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is worth mentioning the transition metal (M) encapsulating silicon super atoms, M@Si 16 , which have been probed in the gas‐phase molecular beam, and predicted by quantum chemical calculations, but not yet isolated [51] . However, the structure of surface‐immobilized M@Si 16 clusters has been elucidated using scanning probe microscopy and photoelectron spectroscopy, glimpsing a way toward future functional materials in the solid state [51–53] …”
Section: Figurementioning
confidence: 99%
“…For example, MSi 16 clusters (M = Sc, Ti and V), which are of high symmetry and stability, were theoretically predicted to form stable hetero-oligomers ScSi 16 -VSi 16 and ScSi 16 -TiSi 16 -VSi 16 [19]. Additionally, TaSi 16 cluster can contact with C 60 cluster through covalence bond and thereby form TaSi 16 -C 60 dimer [20]. On basis of BeSi 12 hexagonal prism, a metalsilicon tubular structure was synthetized [21].…”
Section: Introductionmentioning
confidence: 99%